PENENTUAN STRUKTUR SENYAWA ANTIOKSIDAN LIMONOID DARI BIJI JERUK SAMBAL (Citrus microcarpa Bunge) KALIMANTAN BARAT - Setyo Widayanti; Rudiyansyah Rudiyansyah; Andi Hairil Alimuddin (Indonesian Journal of Pure and Applied Chemistry, 2018)
Limonoid has been isolated from orange seeds of Citrus microcarpa Bunge using extraction and partitioning methods. It is a yellowish-white crystal with a melting point of 276-277 oC. Based on the phytochemical analysis and FTIR spectroscopy, 1H NMR and compared with the literature, the compound is limonin which is a triterpenoid. The purpose of this study was to determine the structure and evaluate antioxidant activity of the limonin. The antioxidant activity by DPPH obtained IC50 value of limonin was 199.18 ppm. Whereas, the test antioxidant activity by FRAP method using a comparative solution of ascorbic acid showed that there was an increasingly blue color change, which meant that antioxidant activity was stronger with activity value of 11.88 mgAAE /g sample.